A Band-Stop Filter-Based LQR Control Method for Semi-Active Seat Suspension to Mitigate Motion Sickness - Zhijun Fu; Mengyang Jia; Zhigang Zhang; Dengfeng Zhao; Jinquan Ding; Subhash Rakheja (Machines, 2025)
This study proposes a novel control framework for semi-active seat suspensions, specifically targeting motion sickness mitigation through precision suppression of vertical vibrations within the 0.1–0.5 Hz frequency range. Firstly, a fractional-order band-stop filter in conjunction with a linear quadratic regulator (LQR) controller under frequency-domain sensitivity constraints (0.1–0.5 Hz) is proposed to achieve frequency-selective vibration attenuation. Secondly, the multi-objective butterfly optimization algorithm (MOBOA) is adopted to optimize the LQR controller’s weighting matrices (Q, R) by balancing conflicting requirements in terms of human body displacement limits, acceleration thresholds, and suspension travel. Finally, experimental validation under concrete pavement excitation and random road profiles demonstrates significant advantages over conventional LQR, i.e., a 41.04% reduction in vertical vibration amplitude and a 55.95% suppression of acceleration peaks within the target frequency band. The combined enhancements offer dual benefits of enhancing ride comfort and motion sickness mitigation in real-world driving scenarios.